Care in everyday life : an ethic of care in practice - Barnes, Marian (Bristol : Policy, 2012)
In this wide-ranging book, Marian Barnes argues for care as an essential value in private lives and public policies, considering the importance of care to well-being and social justice and applying insights from feminist care ethics to care work, and care within personal relationships.
Title from publisher's bibliographic system (viewed on 01 Sep 2022).
Keywords: Social service; Social service -- Moral and ethical aspects; Social policy -- Moral and ethical aspects